ECOLOGY AND ENVIRONMENTAL PROTECTION ARE ONE OF THE MOST IMPORTANT PROBLEMS OF CONCERN TO EVERYONE - Ishankulova K. K.; Shermamatova M. A.; Xalilova F.A. (Western European Studies, 2024)
Today, ecology and environmental protection are one of the most pressing issues that concern everyone. By the end of the last century, as a result of the imbalance between man and nature, the ecological and environmental situation has undergone dramatic changes. This article examines the problems associated with ecology in Uzbekistan and the countries of Central Asia and its sustainable development in Uzbekistan. Explained
Keywords: UN; Central Asia; Republic of Uzbekistan